2022
DOI: 10.3233/jrs-227030
|View full text |Cite
|
Sign up to set email alerts
|

Improving physical health monitoring and interventions in a learning disabilities forensic psychiatric secure service

Abstract: BACKGROUND: Patients in psychiatric inpatient settings are at increased risk of developing physical health complications due to the structure of inpatient wards, the metabolic side-effects of antipsychotic medications and socioeconomic factors. Robust physical health monitoring and interventions are paramount in reducing this health inequality. OBJECTIVE: To improve the quality of physical health interventions in the ward environment and empower patients to follow healthy lifestyle guidance to reduce their ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Except for effects on resting heart rate (HR) and psychological changes, the interventions showed no or minor decreases in body mass index (BMI) and body weight. [35][36][37][38] Glucagon-like peptide 1 (GLP-1) is an incretin hormone secreted from the L cells in the intestinal mucosa in response to nutrients. 39 In a previously published study, we reported that the GLP-1 receptor agonist (GLP-1RA) liraglutide 1.8 mg, administered once daily subcutaneously for 16 weeks to patients diagnosed with prediabetes and schizophrenia spectrum disorders, reduced body weight by 5.3 kg and improved glycated haemoglobin A1c plasma levels (HbA1c) with approximately 0.2% (2.3 mmol/mol), glucose tolerance, and several other cardiometabolic disturbances compared to placebo.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for effects on resting heart rate (HR) and psychological changes, the interventions showed no or minor decreases in body mass index (BMI) and body weight. [35][36][37][38] Glucagon-like peptide 1 (GLP-1) is an incretin hormone secreted from the L cells in the intestinal mucosa in response to nutrients. 39 In a previously published study, we reported that the GLP-1 receptor agonist (GLP-1RA) liraglutide 1.8 mg, administered once daily subcutaneously for 16 weeks to patients diagnosed with prediabetes and schizophrenia spectrum disorders, reduced body weight by 5.3 kg and improved glycated haemoglobin A1c plasma levels (HbA1c) with approximately 0.2% (2.3 mmol/mol), glucose tolerance, and several other cardiometabolic disturbances compared to placebo.…”
Section: Limitationsmentioning
confidence: 99%
“…Different non‐pharmacological interventions have been investigated to mitigate the obesogenic environment in secure settings and forensic psychiatry. Except for effects on resting heart rate (HR) and psychological changes, the interventions showed no or minor decreases in body mass index (BMI) and body weight 35–38 …”
Section: Introductionmentioning
confidence: 99%